PREDICTING THE SUCCESS OF UNIVERSITY GRADUATES IN THE JOB MARKERT - RAJA MASBAR (Jurnal Bisnis dan Akuntansi, 2004)
The purpose of this study is to analyze and to estimate a model of the determinants of absorption level of university graduates t the local job market. In particular, it estimates the success of state university graduates in Sumatera as they are employed by firms (local job market). It utilizes primary data from three universities in Sumatera (Cluster ampling) that represent north, middle, and south regions are Sumatera Utara University (Medan), Andalas University (Padang), and Sriwijawa University (Palembang). This study uses Probit dan Logit. Model to estimate the determinants of absorption level of university graduates at the local job market. Generally, the result of this study shows that gradu tes who have positive attributes are more likely to success than other aduates in the job market.